Explotação e uso do Aqüífero Guarani no Triângulo Mineiro - estudo de caso: Cachoeira Dourada - Rodrigues, Anamaria Moya (2007)
The Guarani Aquifer's study, of its exploitation and use, as its potentialities in the Triângulo Mineiro region, considering the reality that the information about underground waters in the country are scarce and disperse, it constitutes the main focus of this research. The study of case in Cachoeira Dourada, with nine deep tubular wells, and the others six ones, three ones sited in Uberaba, two in Conceição das Alagoas and one in Frutal, totalizing the fifteen tubular well identified in this work, bringing a systematic comprehension of what exist presently, about these exploited waters in the regional delimited context. Between several possible applications, were recognized the use to public supplying, envase, health-resort, hydro-thermotherapy and utilization in the private leisure. The hydro-geochemistry and thermal features, allied at characteristic of these waters, had directed their uses. Nevertheless, the apparent adverse factor of quality, due to high content of salts presented, it became in an attractive tourist, contributing for the exploitation in Cachoeira Dourada, as well as the excellence in the quality it led to the use to human consumption in Uberaba, Conceição das Alagoas and Frutal. The stored water volume estimative in the sandstones of the Guarani Aquifer and the use of geothermic energy simulation demonstrated, beyond of the presentation set's results, incorporated suitable information to major understanding of Guarani Aquifer in the Triângulo Mineiro region.